Dynamic Processes of Parent–Adolescent Conflict and Warmth in Chinese Families: Differences between Mothers and Fathers. - Luo, Xiaohui; Wang, Hui; Xu, Jianjie; Liu, Hongyun; Suveg, Cynthia; Han, Zhuo Rachel (Journal of Youth & Adolescence, 2025)
Parent-adolescent relationships are shaped by daily interactions that include both warmth and conflict, yet most research has focused on aggregate or long-term patterns rather than their day-to-day fluctuations. Guided by family systems theory, this study examined how mothers and fathers distinctly contribute to daily parent-adolescent warmth and conflict, as well as how these interactions vary across families. The sample consisted of 307 Chinese adolescents (M = 13.02 years, SD = 0.762 years; 49.51% girls). Participants reported their daily perceptions of warmth and conflict with both their mothers and fathers over a 10-day period. Dynamic structural equation modeling showed significant autoregressive effects for mother- and father-adolescent warmth and conflict. Cross-lagged analyses revealed that higher levels of mother-adolescent conflict, higher levels of father-adolescent warmth, and lower levels of father-adolescent conflict predicted increased mother-adolescent warmth the following day. Additionally, greater father-adolescent conflict predicted greater mother-adolescent conflict the next day. Within-family effects varied in both direction and magnitude across families and some lagged effects were moderated by adolescent age and family income. Overall, these findings emphasize the importance of considering parent gender and family-level variations when examining daily family dynamics. They also suggest that maternal warmth may be especially sensitive to the family's daily relational experiences, highlighting the need for parenting practices and interventions that acknowledge and address this responsiveness.